2017
DOI: 10.1016/j.jjcc.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of serum cytokine levels in Takayasu arteritis patients: Potential utility as biomarkers for monitoring disease activity

Abstract: Both TNF-α and IL-6 levels, but not IL-12 or IL-23 levels, in the serum could be potent biomarkers that can reflect the activity of TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 30 publications
4
20
0
3
Order By: Relevance
“…Serum IL-23 levels were similar to those of healthy controls in patients with TAK. However, IL-23 levels stayed high in inactive disease, suggesting that it might be a factor for disease relapses, similar to the observations in GCA (58,60).…”
Section: Immune Pathogenesis Of Takayasu Arteritissupporting
confidence: 85%
“…Serum IL-23 levels were similar to those of healthy controls in patients with TAK. However, IL-23 levels stayed high in inactive disease, suggesting that it might be a factor for disease relapses, similar to the observations in GCA (58,60).…”
Section: Immune Pathogenesis Of Takayasu Arteritissupporting
confidence: 85%
“…[18]. A very recent Japanese study has also observed an increase in the levels of IL-6 and TNF-α in TA patients during active phase [19]. However, in yet another study from Turkey, IL-18 but not IL-6 was found to be elevated in active disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the hydrolysis of triglyceride to free fatty acids can also be enhanced through TNF‐α expressed by stimulated PVAT macrophages, forming a loop to evoke inflammation . PVAT inflammation participates in the development of cardiovascular diseases by breaking the homeostasis of vessels, leading to excessive secretion of proinflammatory factors such as IL‐6, IL‐17, leptin, visfatin, and TNF‐α and reduction of anti‐inflammatory factors including adiponectin, angiotensin 1‐7, and IL‐10, and many of these factors have also been reported to contribute to the pathogenesis of TA . To date, there is no definitive evidence showing how PVAT inflammation affects the vascular wall in TA …”
Section: Discussionmentioning
confidence: 99%
“…The etiology of TA is still unknown, although previous studies have shown that both innate and adaptive immune responses, as well as cytokines and chemokines, are involved . A study conducted in Japan suggested that serum levels of monoclonal anti‐tumor necrosis factor‐α (TNF‐α) antibody might be a potent biomarker that can reflect disease activity . Our previous studies showed that interleukin‐6 (IL‐6) was not only a strong marker for active disease but also played a critical role in pathogenesis and vascular fibrosis .…”
Section: Introductionmentioning
confidence: 99%